Kilkenny : a novel - L'Amour, Louis, 1908-1988 (Bantam Books, 2018)
Kilkenny settles in the lonely mountains of Utah after killing a young man who challenged his paid for it with his life. The boy's father is a powerful rancher who is determined to run his vast herd on the limited grasslands in the valley - whether he has to buy out, run out, or kill the local ranchers. He'll cut down anyone in his way - especially a man he already hates for killing his son. Kilkenny's going to have to defend himself against another Tetlow.